The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5935/1676-4285.20144236
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of adolescent women regarding gender diferences: a descriptive study

Abstract: Aims:To understand the perceptions and meanings of being an adolescent woman in our society and to reflect upon the sociocultural construction of these women. Method: This is a field descriptive study, in which a qualitative approach was used, carried out in a public school in Rio Grande do Sul. Nine adolescent women participated in the study. Data collection occurred in June and July 2012 by means of focus groups.For data analysis we used thematic analysis. Result: Relations that teenagers have about sexualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Such disciplinary discourses, focusing on gender issues, have also been noticed in a research conducted with adolescent girls in the south of Brazil (14) , in which teenagers reported that their families treated sexuality very differently when talking to boys than they did when talking to girls. That implies in a higher level of control and regulation exerted by parents to adolescent girls, in addition to giving less freedom to them in daily activities.…”
Section: Discussionmentioning
confidence: 62%
“…Such disciplinary discourses, focusing on gender issues, have also been noticed in a research conducted with adolescent girls in the south of Brazil (14) , in which teenagers reported that their families treated sexuality very differently when talking to boys than they did when talking to girls. That implies in a higher level of control and regulation exerted by parents to adolescent girls, in addition to giving less freedom to them in daily activities.…”
Section: Discussionmentioning
confidence: 62%